Composition and Antibacterial Effect of Mint Flavorings in Candies and Food Supplements - Kapp, Karmen; Orav, Anne; Roasto, Mati; Raal, Ain; Püssa, Tõnu; Vuorela, Heikki; Tammela, Päivi; Vuorela, Pia (Planta Medica, 2020)
Mint flavorings are widely used in confections, beverages, and dairy products. For the first time, mint flavoring composition of mint candies and food supplements (n = 45), originating from 16 countries, as well as their antibacterial properties, was analyzed. The flavorings were isolated by Marcussonʼs type micro-apparatus and analyzed by GC-MS. The total content of the mint flavoring hydrodistilled extracts was in the range of 0.01 – 0.9%. The most abundant compounds identified in the extracts were limonene, 1,8-cineole, menthone, menthofuran, isomenthone, menthol and its isomers, menthyl acetate. The antimicrobial activity of 13 reference substances and 10 selected mint flavoring hydrodistilled extracts was tested on Escherichia coli and Staphylococcus aureus by broth dilution method. Linalool acetate and (−)-carvone, as most active against both bacteria, had the lowest MIC90 values. (+)-Menthyl acetate, (−)-menthyl acetate, and limonene showed no antimicrobial activity. Three of the tested extracts had antimicrobial activity against E. coli and 8 extracts against S. aureus. Their summary antimicrobial activity was not always in concordance with the activities of respective reference substances.
Keywords: Mentha; Lamiaceae; GC-MS; terpenoids; Escherichia coli; Staphylococcus aureus